Tejido propio del pueblo nasa: Un diálogo de saberes con las matemáticas occidentales para el aprendizaje de la geometría en grado cuarto (2023)
This degree work presents a didactic proposal for the teaching and learning of geometry through the dialogue of knowledge with the culture of the Nasa indigenous people, carrying out an ethnomathematical proposal with fourth grade students. This with the aim of evaluating the effectiveness of the TEJIMA strategy, in which nasa tissue is used as a basis for teaching and learning Western mathematics.